ANALISIS AKAR MASALAH DALAM PERENCANAAN PENGELOLAAN DAS TERPADU PALUNG - lafifah, Sitti (Fakultas Kehutanan Institut Pertanian STIPER Yogyakarta, 2012)
Watershed is a complex mega-system, and to manage it in an integrated manner requires a systematic method in searching the root problem. Root cause analysis method (Root Cause Analysis /RCA) is a systematic approach to obtain the real root causes of the complex problems. Determination of the exact root of the problem is key to have a good quality resource management planning. Identification results show that the major issues facing in Palung Watershed is a conflict water resources management. While the negative conditions (Undisired Effects) found in this watershed are limited availability of water resources, weak coordination between sectors, the inefficient pattern of water resources utilization, weak implementation in law enforcement and landuse changing in the region from upstream to downstream. The results of the RCA analysis shows that the problems faced by the Palung Watershed is not caused olny by natural resource degradation and injustice of distribution, but mailny caused by lack of economic activities which is heavily influenced by the educational and cultural aspects. Keywords : Root Cause Analysis, Watersheed, Palung, East Lombok